The Edinburgh companion to twentieth-century philosophies - Boundas, Constantin V. (Edinburgh University Press, 2007)
The Companion is organized into two sections, each one of which reflects the developments of the Anglo-American Analytic and the Continental European philosophical traditions respectively. An appendix presents the main accomplishments of non-Western philosophies in the same time frame. Each section discusses the main movements and fields of the discipline throughout the century. The authors have maintained a balance between the historian's commitment to breadth and accuracy with the commitment of the systematic philosopher to the engaged point of view and to critical reflection. The result is a distinctive reference book made up of a series of philosophical studies -an invaluable companion to anyone who is searching for a panoramic but also reliable and challenging presentation of the philosophical ideas which shaped the last century.